1974
DOI: 10.1084/jem.140.4.1068
|View full text |Cite
|
Sign up to set email alerts
|

The Involvement of Lactoferrin in the Hyposideremia of Acute Inflammation

Abstract: The hyposideremia of inflammation was found to be based on a three-step mechanism involving lactoferrin, the iron-binding protein from the specific granules of neutrophilic leukocytes. (a) Lactoferrin is Released from Neutrophils in an Iron-Free Form. When phagocytosis was induced in neutrophils by zymosan or bacteria, lactoferrin was recovered in the incubation medium together with other constituents of the specific granules, such as alkaline phosphatase and lysozyme. Lactoferrin extracted from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
129
1
2

Year Published

1976
1976
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 279 publications
(136 citation statements)
references
References 28 publications
(38 reference statements)
3
129
1
2
Order By: Relevance
“…The present work confirms and extends our previous observations that FeLf has a high affinity for the membrane of macrophages (18,19). Previous experiments had shown that human Lf which was injected into rats was quickly removed by the RES with a clearance rate dependent upon the iron content of the protein and its structural integrity.…”
Section: Comparison Of the Binding Of Felf To Various Mouse Cells ~2supporting
confidence: 81%
“…The present work confirms and extends our previous observations that FeLf has a high affinity for the membrane of macrophages (18,19). Previous experiments had shown that human Lf which was injected into rats was quickly removed by the RES with a clearance rate dependent upon the iron content of the protein and its structural integrity.…”
Section: Comparison Of the Binding Of Felf To Various Mouse Cells ~2supporting
confidence: 81%
“…In such an environment iron exchange from transferrin is easier due to the lower pH suggesting that lactoferrin may contribute to local iron accumulation at sites of inflammation (Brock, 2002). Lactoferrin has long been known to be responsible for hypoferraemia through binding free iron and shuttling it back to macrophages (Van Snick et al, 1974).…”
Section: Lactoferrin and Iron Metabolismmentioning
confidence: 99%
“…Lactoferrin retains a high affinity for iron at pH values <4.5, unlike transferrin, which loses its affinity for iron at pH <5.0. At a low pH, lactoferrin may even obtain iron by exchange from transferrin [39]. Since in sputum the concentrations of lactoferrin are similar as those of transferrin (figs.…”
Section: Discussionmentioning
confidence: 99%